Improving eye–computer interaction interface design: Ergonomic investigations of the optimum target size and gaze-triggering dwell time - Ya-feng Niu; Yue Gao; Cheng-qi Xue; Ya-ting Zhang; Li-xin Yang (Journal of Eye Movement Research)
The Midas touch is reflected by the interactive feedback of interface functional elements, and a low level of spatial accuracy is related to the interaction area. This study tried to solve these two problems from the perspective of human-computer interactions and ergonomics. Two experiments were conducted to explore the optimum target size and gaze-triggering dwell time of the eye–computer interaction (ECI) system. Experimental Series 1 was used as the pre-experiment to identify the size that has a greater task completion rate. Experimental Series 2 was used as the main experiment to investigate the optimum gaze-triggering dwell time by using a comprehensive evaluation of the task completion rate, reaction time, and NASA-TLX (Task Load Index). In Experimental Series 1, the optimal element size was determined to be 256 × 256p x2. The conclusion of Experimental Series 2 was that when the dwell time is set to 600 ms, the efficiency of the interface is the highest, and the task load of subjects is minimal as well. Finally, the results of Experiment Series 1 and 2 have positive effects on improving the usability of the interface. The optimal control size and the optimal dwell time obtained from the experiments have certain reference and application value for interface design and software development of the ECI system.